Analisis Rasio Profitabilitas saat sebelum dan sesudah Covid-19 pada PT. Blue Bird Tbk - Naufal Henry Maulidhani (CV. ITTC INDONESIA, 2024)
This research was intended to carry out an analysis of profitability ratios Blue Bird 2019-2023. Covid-19 has had a major influence on the decline is a number of companies in the goods and services sector, especially serving public transportation. The research method used is descriptive quality methods, using secondary data originating from the Indonesian Stock Exchange. The sample studied was calculating the profitability ratio of PT. Blue Bird 2019-2023. Data analysis techniques using Profit Margin, Return On Assets and Return On Equity methods. Based on research results, Covid-19 has an influence on the profitability ratio at PT. Blue Bird Tbk.